BOT-TE: Advanced Multi-purpose Land Rover with Image Processing - Dhanagopal R, Sureshkumar R, Menaka R, Faizan Ul Haq (International Journal of Advanced Science and Technology, 2020)
Most of the modern multi-terrain vehicles has used various chassis designs to tackle extreme terrains. In which some of the rovers make use of various sensors for the analysis of structures and obstacles in the path of the rover. However, the major computational part for the analysis is carried out by the controller (of the drone/rover). The controller for these rovers is designed on an application specific basis, i.e. for executing an image processing algorithm we may use a specific IC. On the other hand, for controlling the motor we may require a totally different IC. In order to avoid this problem,we may utilize the SoC (system on chip) that are capable of handling both these functionality. Hence, thecomputational power in a controller is not too high at the MPU or CPU of the rover/drone. This paper proposes the cloud computing as a solution to optimize its working and analyze the problem efficiently. Recognition of threat as well as obstacle avoidance based on image processing and other features involving image processing/ machine learning in drones/ rovers is typically an on-board operation.The algorithms apply the weights that can’t be monitored by the user and each time the program is fed to the system, it has to return to user for any updates.In this system there is no need for updates. BOT-TE can update its algorithm based on requirement for any given scenario; this paves way for an entirely new domain to further develop technology for remote firmware updates. A rover with such a path predictive algorithm can allow the creation of temporary structures and grid formation in emergency situation based on requirement.